TLR3 Ligand PolyI:C Prevents Acute Pancreatitis Through the Interferon-β/Interferon-α/β Receptor Signaling Pathway in a Caerulein-Induced Pancreatitis Mouse Model - Huang, Chaohao; Chen, Shengchuan; Zhang, Tan; Li, Dapei; Huang, Zhonglin; Huang, Jian; Qin, Yanghua; Chen, Bicheng; Cheng, Genhong; Ma, Feng; Zhou, Mengtao (Frontiers in Immunology, 2019)
Acute pancreatitis (AP) is a common and devastating inflammatory disorder of the pancreas. However, there are still no effective treatments available for the disease. Therefore, it is important to discover new therapeutic targets and strategies for better treatment and prognosis of AP patients. Toll-like receptor 3 (TLR3) ligand polyI:C is a double-stranded RNA mimic that can be used as an immune stimulant. Our current study indicates that polyI:C exerted excellent anti-inflammatory effects in a caerulein-induced AP mouse model and taurocholate-induced pancreatic acinar cell line injury model. We found that polyI:C triggers type I interferon (IFN) production and downstream IFN-α/β receptor (IFNAR)-dependent signaling, which play key roles in protecting the pancreas from inflammatory injury. Knockout of IFN-β and IFNAR in mice abolished the preventive effects of polyI:C on caerulein-induced AP symptoms, which include pancreatic edema, neutrophil infiltration, the accumulation of reactive oxygen species (ROS), and inflammatory gene expression. Treating pancreatic acinar 266-6 cells with an IFNAR inhibitor, which blocks the interaction between type I IFN and IFNAR, diminishes the downregulation of oxidative stress by polyI:C. Additionally, a subsequent transcriptome analysis on the role of polyI:C in treating pancreatitis suggested that chemotaxis of neutrophils and the production of ROS were inhibited by polyI:C in the pancreases damaged by caerulein injection. Thus, polyI:C may act as a type I IFN inducer to alleviate AP, and it has the potential to be a promising therapeutic agent used at the early stages of AP.